2014
DOI: 10.1186/1471-2334-14-346
|View full text |Cite
|
Sign up to set email alerts
|

Significant cross reactive antibodies to influenza virus in adults and children during a period of marked antigenic drift

Abstract: BackgroundLittle is known about the development of cross-reactive antibodies following natural exposure to pathogens. Such knowledge is critical in the development of new universal influenza vaccines.MethodsTo study the possibility of the presence of cross-reactive antibodies to influenza viruses which underwent a major antigenic drift between the years 1999 and 2007 sera from samples of 80 children and 400 adults were selected at random from the Israeli national serum bank. The sera was obtained in 2002 and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…He et al ., observed that repeated immunization with inactivated A(H1N1)pdm09 vaccine resulted in reduced vaccine-specific and cross-reactive plasma-blast derived antibody responses 37 . As a corollary to these studies cross reactive H3N2 antibodies have been described in sera collected just after periods of marked antigenic drift 38 .…”
Section: Discussionmentioning
confidence: 93%
“…He et al ., observed that repeated immunization with inactivated A(H1N1)pdm09 vaccine resulted in reduced vaccine-specific and cross-reactive plasma-blast derived antibody responses 37 . As a corollary to these studies cross reactive H3N2 antibodies have been described in sera collected just after periods of marked antigenic drift 38 .…”
Section: Discussionmentioning
confidence: 93%
“…We did not assess subjects for pre-existing immunity to other influenza strains, including those that had been employed in influenza vaccination in previous years for logistical reasons. However, prior exposure may well have influenced the outcome of vaccination, since cross-reactivity between influenza viruses is well documented ( 55 ) and pre-existing immunity to flavivirus has been demonstrated to influence the response to yellow fever vaccination ( 56 ). Future work characterizing in detail the influence of both pre-existing immunosenescence and pre-existing immunity on vaccination outcome is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with our observation that antibodies present in the sera of vaccinated individuals were significantly less efficient in neutralizing the Israeli influenza A(H3N2) infection. We previously reported that naturally occurring antibodies cross react with several influenza viruses [ 13 ]. Some antibody cross-reactivity was found between the Israeli influenza A(H3N2) virus and the A/Texas/50/2012 virus, however it may have been insufficient in modifying the course of infection with the circulating novel influenza A(H3N2) in Israel.…”
Section: Discussionmentioning
confidence: 99%